A Longitudinal Study on Adherence to Anti Retroviral Therapy and Its Determinants in Telangana State - Misha Gorantla; Varun M Malhotra; Nagaraj Kondagunta (National Journal of Community Medicine, 2019)
Introduction: India is among the list of countries with highest HIV prevalence. Adequate viral suppression requires strict adherence  to antiretroviral therapy (ART). This research was conducted to study the clinico-demographic profile of study population and to study the barriers to treatment adherence.